(untitled) (Dermatology Reports, 2016)
Repairing surgical defects of the nasal tip is challenging, mainly because of the lack of freely mobile skin available peripherally. The Peng flap is a one-stage cutaneous flap that circumvents this difficulty by recruiting skin from the nasal dorsum and sidewall regions. The design produces a tridimensional shape perfectly adapted to the configuration of the nasal tip and allows for an inconspicuous closure of the defect. We present three examples of full-thickness skin defects involving the nasal tip, reconstructed using a modified version of the Peng flap, and present the experience at our department with this surgical technique.